Enhancing mechanical and thermal properties of PVA-abaca fiber biocomposites via ultrasonic vibration bath treatment - Mochamad Asrofi; Nur Achmad Asyari; Revvan Rifada Pradiza; Muhammad Abduh; Muhammad Yusuf; Melbi Mahardika; R.A. Ilyas; M.R.M. Asyraf; S.M. Sapuan; Victor Feizal Knight; Mohd Nor Faiz Norrrahim (Results in Engineering)
This research investigates about the properties of polyvinyl alcohol (PVA) based biocomposite with abaca fiber as filler. The amount weight fraction of fibers and matrix were kept constant 10 and 90 wt% with a total weight of 10 g of biocomposite, respectively. The biocomposites was produced by solution casting method. The novel strategies in this study were ultrasonic vibration bath (UVB) treatment. The vibration time of ultrasonic bath was varied 0, 55, 60 and 65 min. This treatment was carried out on biocomposites during gelatinization phase. Tensile test was studied to determine the tensile strength of biocomposites. Meanwhile, scanning electron microscopy (SEM) was used to observe the fracture surface of biocomposite. Others characterization such as thermogravimetric analysis (TGA), fourier transform infrared (FTIR) and x-ray diffraction (XRD) were done to prove the thermal stability, chemical group, and crystallinity index, respectively. The results show the highest tensile strength was obtained in the 65 min UVB samples for 9.13 MPa. This was evidenced by SEM observation indicating more compact structure and good fiber distribution. TGA also showed an increase in thermal stability of around 11.3 °C especially in the 65 min sample compared to 0 min. Some of these results were confirmed by the results of increasing the crystallinity index and the appearance of OH groups in XRD and FTIR characterization, respectively. This method can be used as an alternative to improve the properties of biocomposites compared to chemical treatment.